Listening in Three Acts: Thinking, responding, doing Act 3. (18th August 2021) - Grehan, Helena
Abstract : These three short pieces consider listening and the impacts of refusing to listen in different contexts. Act I engages with this process within the Academy and offers some ideas on how we, as scholars, artists, critics and teachers, might respond. Act II reflects on the deep listening evident in Nick Cave's replies to his fans, in his Red Hand Files . Act III engages with Josephine Wilson's provocation in response to Christoph Büchel's Barcha Nostra at the end of her essay 'Shipwreck without Label' in On Politics to drown spectators at the Venice Biennale. Throughout these pieces I try to uncover moments of ethical attunement and to think-through the value of this practice – of being ethically attuned - which I interpret as one of deep listening.